Odpowiedzi

2010-01-26T17:41:18+01:00
X(x+6)-9=x(x-1)+1
x^2+6x-9=x^2-x+1
6x+x=1+9
7x=10/:7
x=1i3/10


3(x+2)-2=4(x-1)+5
3x+6-2=4x-4+5
3x-4x=-4+5-6+2
-x=-3/:-1
x=3
Najlepsza Odpowiedź!
2010-01-26T17:41:48+01:00
1. x²+ 6x -9 = x² - x +1 (x² się redukuje)
6x-9= -x +1
6x+x=1+9
7x=10 /:7
x= 10/7

2. 3x+6-2= 4x-4 +5
3x -4x = -4+5+2-6
-x= -3 /* (-1)
x=3
2010-01-26T17:42:13+01:00
X(x+6)-9=x(x-1)+1
x²+6x-9=x²-x+1
x²-x²+6x+x=1+9
7x=10 /:7
x=10/7

sprawdzenie
(10/7)*(10/7 +6)-9=(10/7)*(10/7 -1)+1
(10/7)*(10/7 +42/7) -9=(10/7)*(10/7 -7/7) +1
(10/7)*(52/7) -9=(10/7)*(3/7) +1
520/49 -441/49=30/49 +49/49
79/49 = 79/49
L=P

3(x+2)-2=4(x-1)+5
3x+6-2=4x-4+5
3x-4x=1-4
-x=-3 /:(-1)
x=3

sprawdzenie
3(3+2)-2=4(3-1)+5
3*5-2=4*2+5
15-2=8+5
13=13
L=P